2023
DOI: 10.3389/fpls.2023.1189038
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and identification of stress-responsive genes of the CCCH zinc finger family in Capsicum annuum L.

Abstract: The CCCH zinc finger gene family encodes a class of proteins that can bind to both DNA and RNA, and an increasing number of studies have demonstrated that the CCCH gene family plays a key role in growth and development and responses to environmental stress. Here, we identified 57 CCCH genes in the pepper (Capsicum annuum L.) genome and explored the evolution and function of the CCCH gene family in C. annuum. Substantial variation was observed in the structure of these CCCH genes, and the number of exons ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…So far, detailed information on the C3H family in potato has not been uncovered. In this study, we identified and characterized 50 C3H genes from the potato genome, which were similar to those identified in other Solanaceae species, Solanum lycopersicum (47 members) and Capsicum annuum (57 members) [ 47 , 53 ]. The number of C3H genes varies among plant species, for example, rose (31 members) and Medicago truncatula (34 members) have fewer C3H members, and the number of C3H genes in Brassica rapa (103 members) and Glycine max (116 members) are significantly higher than those in other species [ 47 , 52 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…So far, detailed information on the C3H family in potato has not been uncovered. In this study, we identified and characterized 50 C3H genes from the potato genome, which were similar to those identified in other Solanaceae species, Solanum lycopersicum (47 members) and Capsicum annuum (57 members) [ 47 , 53 ]. The number of C3H genes varies among plant species, for example, rose (31 members) and Medicago truncatula (34 members) have fewer C3H members, and the number of C3H genes in Brassica rapa (103 members) and Glycine max (116 members) are significantly higher than those in other species [ 47 , 52 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we identified and characterized 50 C3H genes from the potato genome, which were similar to those identified in other Solanaceae species, Solanum lycopersicum (47 members) and Capsicum annuum (57 members) [ 47 , 53 ]. The number of C3H genes varies among plant species, for example, rose (31 members) and Medicago truncatula (34 members) have fewer C3H members, and the number of C3H genes in Brassica rapa (103 members) and Glycine max (116 members) are significantly higher than those in other species [ 47 , 52 , 54 , 55 , 56 ]. Gene duplication is essential for the adaptation and evolution of organisms, and segmental and tandem duplications are considered to play important roles in the expansion of plant gene families [ 57 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations